HUBUNGAN ANTARA AKUNTANSI AKTIVA TETAP DAN KINERJA KEUANGAN PT. NADIA TRIMANDIRI MULIA DARI TAHUN 2011 - 2015 - Hendrawati; Suhenti (Jurnal Multidisiplin Borobudur, 2023)
This study aims to determine the relationship between fixed asset accounting and the financial performance of PT. Nadia Trimandiri Mulia during the period from 2011 to 2015. The research design used in this study is associative research. The data source used in this study is secondary data. The secondary data in this study consists of the financial statements of PT. Nadia Trimandiri Mulia for the period from 2011 to 2015. The data analysis technique used in this study is descriptive analysis (descriptive statistics). The results of this study indicate the relationship between depreciation expenses and financial performance at PT. Nadia Trimandiri Mulia using the Straight-Line Method, Declining Balance Method, and Sum-of-the-Years'-Digits Method, which can be explained as follows: 1) The efficiency ratio (activity ratio) from 2011 to 2015 has decreased, and the efficiency ratio in 2012 only has a high turnover overall, indicating that management's ability to achieve sales revenue needs to be further improved, 2) A significant decrease in profitability ratios (profitability ratios) was observed in 2014. However, overall, management's ability to obtain profits is very good and balanced, 3) The leverage ratio (solvency ratio) is consistent from 2011 to 2012, while the leverage ratio (solvency ratio) from 2013 to 2015 has experienced a significant decline, indicating that the company's ability to meet short-term/long-term obligations is very good, as seen from the calculation of the leverage ratio (solvency ratio), and the risk of loss suffered by the company is also small.